Powering Qatar’s agricultural growth: Examining the link between electricity prices and development - Shannak, Sa’d; Surkatti, Riham; Al-Kuwari, Mohammad; Amhamed, Abdulkarem (Frontiers in Environmental Science, 2023)
This study analyzes the impact of electricity prices on the development of the agriculture sector in Qatar, using annual data from 2003-2019. Its findings contribute to addressing a gap in current literature and offer valuable perspectives on the sector's obstacles and potential prospects. An extended Cobb-Douglas production function was employed as a theoretical framework, in conjunction with several econometric techniques, including Fully Modified Least Squares, Dynamic Ordinary Least Square, Canonical Cointegration Regression, and Gets, to analyze the persistent relationship between electricity prices, and the gross value added of the agriculture sector. Our research found that electricity prices exert a positive effect on agricultural development. Although the magnitude of the impact was small over the long term, it remained statistically significant. Specifically, the elasticity of the electricity prices ranged between 0.097-0.11, whereas the elasticity of another examined variable, labor productivity, was also positive and ranged between 0.67-0.74. These empirical findings support the ongoing government policy to reform energy prices, increase vegetable production using modernized hydroponic systems, and reduce groundwater use for irrigation, among other policies to sustain food production. Clearly, if these policy options are managed properly, the agriculture sector can play a significant role in diversifying the economy, maintaining environmental conditions and improving food sustainability.